Evaluation of Surgical Resection and Reconstruction Outcomes in Patients with Various Histological Subtypes of Soft Tissue Sarcomas: A Prospective Cohort Analysis: Surgical Outcomes in Soft Tissue Sarcoma - Fatima, Samia; Akhlaque, Roomana; Nasrullah, Muhammad; Amin, Muhammad; Imdad, Sana; Imran, Muhammad (Pakistan Journal of Health Sciences, 2024)
Soft-tissue sarcomas (STS) are rare, especially as histological subtypes (more than 50). Despite being more prevalent in youngsters, their prevalence rises with age. Objective: To analyze the outcomes of surgical resection and subsequent reconstruction in patients with different histological subtypes of soft tissue sarcomas, focusing on the complications, recurrence rates, and overall survival. Methods: A prospective cohort study was conducted and data were collected from 14 patients treated between 2018 to 2022 at the Department of Plastic and Reconstructive Surgery, General Hospital, Lahore. The data included a detailed analysis of patient demographics, histological subtypes, surgical techniques, and postoperative outcomes, including complications, recurrence rates, and overall survival. Results: Soft tissue sarcoma was identified in 2 scalps, 2 arms, 3 forearms, 2 abdominal walls, 3 lower limbs, 1 nape of the neck, and 1 lumbar area. Two patients received neoadjuvant radiation and one chemotherapy. The tumors were 5–17.5 cm wide. Pleomorphic sarcoma was the most prevalent STS subtype, followed by liposarcoma and leiomyosarcoma in histology. This six-patient technique employed Latissimus dorsi, radial forearms, musculocutaneous gastrocnemius, free anterior lateral thigh (ALT) muscles, and year-end median. Complications occurred in 3 out of 14 patients who received flap reconstruction (complete flap failure in one patient, seroma in one patient, infection in one patient). The recurrence rate was 4 (28.6%) and survival rate was 13 (92.9%). Conclusions: This study concluded that R0 resection followed by immediate soft tissue reconstruction has helped in the management of such complex cases in terms of less complications and recurrence rate.